Expression and enzymatic activity of dipeptidyl peptidase-IV in human astrocytic tumours are associated with tumour grade - Stremenova, Jarmila; Krepela, Evzen; Mares, Vladislav; Trim, Julie; Dbaly, Vladimir; Marek, Josef; Vanickova, Zdislava; Lisa, Vera; Yea, Chris; Sedo, Aleksi (International journal of oncology, 2007)
Alterations in dipeptidyl peptidase-IV (DPP-IV) enzymatic activity are characteristic of malignant transformation. Through its well-characterized functionality in regulating the activity of bioactive peptides by removal of the N-terminal dipeptide, DPP-IV activity may have profound effects upon metastatic potential and cell growth. Although DPP-IV/CD26 (EC 3.4.14.5) is the canonical representative of the group, a number of other proteins including DPP-7, 8, 9, and seprase/fibroblast activation protein-alpha (FAP-alpha) have been shown to have similar enzymatic activity. This study was set up to address the relative representation and enzymatic activity of plasma membrane localized DPP-IV/CD26 and FAP-alpha in human brain and astrocytic tumours. In parallel, expression of CXCR4, receptor for glioma cell growth stimulator chemokine SDF-1alpha known to be a DPP-IV substrate, was investigated. This is the first report showing that non-malignant brain tissue contains a DPP-IV-like enzymatic activity attributable mostly to DPP-8/9, while the substantial part of the activity in glioma is due to increased DPP-IV/CD26, localized in both the vascular and parenchymal compartments. DPP-IV enzymatic activity increased dramatically with tumour grade severity. A grade-related increase in CXCR4 receptor paralleled the rise in DPP-IV expression and activity. These data might support a role for DPP-IV regulation of the CXCR4-SDF-1alpha axis in glioma development.
Keywords: buněčná membrána; nádory mozku; Membrane Proteins; Humans; messenger RNA; Tumor Cells, Cultured; lidé středního věku; Brain Neoplasms; Serine Endopeptidases; regulace genové exprese enzymů; Biomarkers, Tumor; Dipeptidyl Peptidase 4; Immunoenzyme Techniques; Female; Aged; dospělí; endopeptidasy; polymerázová řetězová reakce s reverzní transkripcí; Endopeptidases; senioři; lidé; Reverse Transcriptase Polymerase Chain Reaction; želatinasy; Antigens, Neoplasm; Receptors, CXCR4; Astrocytoma; nádorové buňky kultivované; antigeny nádorové; nádorové biomarkery; RNA, Neoplasm; Adult; imunoenzymatické techniky; RNA, Messenger; dipeptidylpeptidasa 4; RNA nádorová; receptory CXCR4; ženské pohlaví; serinové endopeptidasy; Male; Middle Aged; membránové proteiny; Gene Expression Regulation, Enzymologic; Cell Membrane; Gelatinases; mužské pohlaví; astrocytom